Can Active Labour Market Policies Combat Youth Unemployment? - Jonas Maibom Pedersen; Michael Rosholm; Michael Svarer (Institute for the Study of Labor (IZA), 2014)
Active labour market policies (ALMPs) may play an important role in preventing an increase in long-term unemployment following the Great Recession. We consider this issue for Denmark, a country relying extensively on this instrument. We present evidence on the effectiveness of ALMPs as a way of fighting youth unemployment using results from a randomised controlled trial (RCT) that intensified the use of ALMPs. The intervention was conducted after the onset of the financial crisis, and the findings are relatively unfavourable in the sense that further intensification of an already quite intensive effort for youth did not increase employment. In addition, the intensification of ALMPs seems to have in-creased transitions into sickness benefits.
Keywords: J0; J64; 330; youth unemployment; activation; random controlled experiments